Five year incidence of visual field loss in adult chinese: he Beijing eye study - Wang, Ya Xing; Xu, Liang; Jonas, Jost B. (PLOS ONE, 2012)
Purpose To describe the cumulative 5 year incidence of visual field loss in adult Chinese in Greater Beijing. Methods The Beijing Eye Study 2006 included 3251 subjects (mean age 60.4±10.1 years) who had participated in the Beijing Eye Study 2001 and returned for re-examination. All participants underwent a comprehensive eye examination, including visual field test by frequency doubling threshold perimetry. An abnormal visual field was defined as reduced sensitivity in at least one test location. Incident visual field loss was defined as a change in visual field from normal at baseline to abnormal at follow-up. Results An incident visual field loss was detected in 273 eyes (4.3±0.5%) /235 subjects (7.3±0.5%). It was significantly associated with higher age (P = 0.001), higher intraocular pressure (P<0.001), and higher fasting blood glucose concentration (P = 0.019). Considering only eyes (n = 140) with a detected cause for visual field loss, the most frequent causes were cataract (68 (48.6%) eyes) followed by glaucoma (23 (16.4%) eyes), diabetic retinopathy (13 (9.3%) eyes), age-related macular degeneration (10 (7.1%) eyes), and myopic degenerative retinopathy (9 (6.4%) eyes). For 133 (48.7%) eyes with a visual field loss, the cause for the VFL remained unclear. Conclusions The 5-year incidence of visual field loss was 4.3±0.5% per eye or 7.3±0.5% per subject. It increased significantly with age, intraocular pressure, and fasting blood glucose level. Major causes for the incidence of visual field loss were cataract, glaucoma and diabetic retinopathy.